PENGARUH PENDIDIKAN AGAMA HINDU TERHADAP KECERDASAN EMOSIONAL (EQ) SISWA: THE EFFECT OF HINDU RELIGIOUS EDUCATION ON STUDENTS' EMOTIONAL INTELLIGENCE (EQ) - I Putu Merta (UHN I Gusti Bagus Sugriwa Denpasar, 2022)
Children who have just reached the age of teenagers have emotions that are still unstable in determining attitudes and are still easily influenced. And each child develops with its own characteristics. But in life and in relationships, emotions are needed as an activating energy for ethical values such as trust, integrity, empathy, tenacity and credibility, as well as for social capital, which is able to build and maintain mutually beneficial and trusting relationships.This study aims to determine the results of Hindu religious education, the level of emotional intelligence, and the correlation between Hindu religious education and the emotional intelligence of students in Junior High School. The subject studied 197 students, which were determined based on the Krejcie table, Warwick and Lininger formulas with proportional random sampling technique. The measurement of Hindu religious education uses the method of recording student learning outcomes. The instrument of emotional intelligence level is a closed category questionnaire with a vulnerable score of 1 to 5. The analytical technique used in this study is descriptive analysis, moment correlation with a rough number formula. This study found (1) the learning outcomes of students' Hindu religious education were in the medium category with an average of 75.40 from the ideal maximum value of 100; (2) the level of emotional intelligence of students is in the neutral category with an average of 124.66 from the ideal maximum score of 175; and (3) a positive and significant relationship between Hindu religious education and the level of emotional intelligence of students.After going through the research, namely the process of preparing instruments, testing instruments, collecting data and analyzing data, it can be concluded that the learning outcomes of Hindu Religious Education students are in the medium category with an average of 75.40. The emotional intelligence level of the students was in the neutral category with an average of 124.66. And it is clear that there is a positive and significant relationship between the learning outcomes of Hindu religious education on the level of emotional intelligence of students with the results of rcount = 0.159, meaning that increasing the learning outcomes of Hindu religious education will also increase the level of emotional intelligence of students.